Correlation between allergic diseases and lung cancer: a systematic review and meta-analysis - Kunpeng Yang; Kunpeng Yang; Hui Zhao; Lei Wang; Chenglun Cai; Peiyun Lv; Bao Wang; Bao Wang; Bao Wang (Frontiers in Medicine)
ObjectivesThis meta-analysis aims to investigate the potential association between allergic diseases and lung cancer.MethodsA systematic search was conducted in PubMed, Cochrane Library, Embase, and Web of Science databases up to October 8, 2024. Data analysis was performed using Stata 14.0, employing fixed or random effects models based on heterogeneity (p > 0.1, I2 ≤ 50% or I2 > 50%). Subgroup and sensitivity analyses were conducted, and publication bias was assessed.ResultsAnalysis of 10 studies revealed a negative association between allergic diseases and lung cancer risk (OR: 0.75, 95% CI: 0.66–0.85, I2 = 74.4%, p < 0.001). Subgroup analyses showed eczema was not statistically associated with lung cancer (OR = 0.73; 95% CI: 0.51–1.06), while allergic rhinitis showed negative correlation (OR = 0.74; 95% CI: 0.64–0.86). Both men (OR = 0.56; 95% CI: 0.44–0.71) and women (OR = 0.71; 95% CI: 0.54–0.94) with allergic diseases demonstrated reduced lung cancer risk.ConclusionAllergic diseases are inversely associated with lung cancer risk, with allergic rhinitis acting as a protective factor, while eczema shows no significant association. Further epidemiological studies are warranted.Systematic review registrationhttps://inplasy.com/inplasy-2024-11-0086/, identifier INPLASY2024110086.